2010 IEEE Vehicle Power and Propulsion Conference 2010
DOI: 10.1109/vppc.2010.5728985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the benefits of using dual-source energy storage in hybrid electric vehicles

Abstract: Batteries are often used as energy storage in hybrid and electric vehicles. Despite of the development, technical characteristics of batteries are the most limiting factor for further increasing the energy conversion efficiency and pure electric operation of these vehicles. In this research, dual-source energy storage system, a battery pack and ultracapacitors, has been studied by simulation of hybrid city bus models. These two different types of energy storages have complementary characteristics therefore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…A combination of two different types of energy storage technologies, typically a battery and ultracapacitors, offers an advantageous practical performance and reduced power demands on the battery. Research has been actively carried out in this area for fuel cell vehicles [1], [8], [9], heavy hybrid vehicles [10], [11], and for electric car applications [12], [13]. A hybrid ESS can be quite complex from the design point of view, and it is not necessarily the most cost-effective solution.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of two different types of energy storage technologies, typically a battery and ultracapacitors, offers an advantageous practical performance and reduced power demands on the battery. Research has been actively carried out in this area for fuel cell vehicles [1], [8], [9], heavy hybrid vehicles [10], [11], and for electric car applications [12], [13]. A hybrid ESS can be quite complex from the design point of view, and it is not necessarily the most cost-effective solution.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, most of the research evaluated the hybrid battery and supercapacitor storage systems for electric vehicles [21][22]. It has been reported that the hybrid supercapacitor and battery storage system fulfills the peak power needs and extends the battery life [23][24][25][26]. In addition, hydrogen fuel cell storage, flywheel storage, and superconducting magnetic energy storage has been studied by many scientists.…”
Section: Overview Of Existing Storage Systems For Electric Vehiclesmentioning
confidence: 99%
“…These rules are implemented by using the lookup table in order to distribute the required power between ICE and EM. The methodology of deterministic rule based (DRB) controller and its implementation on the HEVs is presented in [15][16][17][18][19]. The optimization method to evaluate the components' size as well as the control parameters for different HEVs that allows to reduce the mean value of fuel consumption of the whole driving cycle, where the controller uses a DRB strategy, is introduced in [20][21][22].…”
Section: Deterministic Rule Based Control Strategymentioning
confidence: 99%